7-(4-Fluorobenzylamino)-2-phenyl-1,2,4-triazolo[1,5-a][1,3,5]triazin-5-amine methanol disolvate - Dolzhenko, Anton; Tan, G.; Koh, L.; Dolzhenko, A.; Chui, W. (Blackwell Munksgaard, 2011)
THe 1,2,4-triazolo[1,5-a][1,3,5]triazine system in the title compound, C17H14FN7.2CH3OH, is essentially planar, with an r.m.s. deviation of 0.0215 A. The attached phenyl ring lies almost in the mean plane of the heterocyclic core [dihedral angle = 3.56 (4)deg]. In the crystal, centrosymmetric inversion dimers connected via intermolecular N=H...N hydrogen bonds between H atom of the primary amino group and the triazine N atom [R22(8) graph-set motif] form sheets parallel to (010). A second set of dimers connected via N=H...F hydrogen bonds between the other H atom of the primaryamino group and the F atom forms an R22(24) graph-set motif linking the sheets. Methanol solvent molecules are packed in channels running along the [010] direction.